A randomised controlled study of the effectiveness of breathing retraining exercises taught by a physiotherapist either by instructional DVD or in face-to-face sessions in the management of asthma in adults - Thomas, M; Bruton, A; Little, P; Holgate, S; Lee, A; Yardley, L; George, S; Raftery, J; Versnel, J; Price, D; Pavord, I; Djukanovic, R; et al. (NIHR Journals Library, 2017)
Asthma control is suboptimal, resulting in quality of life (QoL) impairment and costs. Breathing retraining exercises have evidence of effectiveness as adjuvant treatment, but are infrequently used. To transfer the contents of a brief (three-session) physiotherapist-delivered breathing retraining programme to a digital versatile disc (DVD) and booklet format; to compare the effectiveness of the self-guided intervention with that of 'face-to-face' physiotherapy and usual care for QoL and other asthma-related outcomes; to perform a health economic assessment of both interventions; and to perform a process evaluation using quantitative and qualitative methods. Parallel-group three-arm randomised controlled trial. General practice surgeries in the UK. In total, 655 adults currently receiving asthma treatment with impaired asthma-related QoL were randomly allocated to the DVD (n = 261), physiotherapist (n = 132) and control (usual care) (n = 262) arms in a 2 : 1 : 2 ratio. It was not possible to blind participants but data collection and analysis were performed blinded. Physiotherapy-based breathing retraining delivered through three 'face-to-face' respiratory physiotherapist sessions or a self-guided programme (DVD plus our theory-based behaviour change booklet) developed by the research team, with a control of usual care. The primary outcome measure was asthma-specific QoL, measured using the Asthma Quality of Life Questionnaire (AQLQ). Secondary outcomes included asthma symptom control [Asthma Control Questionnaire (ACQ)], psychological state [Hospital Anxiety and Depression Scale (HADS)], hyperventilation symptoms (Nijmegen questionnaire), generic QoL [EuroQol-5 Dimensions (EQ-5D)], assessments of airway physiology (spirometry) and inflammation (exhaled nitric oxide) and health resource use and costs. Assessments were carried out at baseline and at 3, 6 and 12 months post randomisation. Patient engagement and experience were also assessed using quantitative and qualitative methods. Primary efficacy analysis was between-group comparison of changes in AQLQ scores from baseline to 12 months in the intention-to-treat population with adjustments for prespecified covariates. Significant improvements occurred in the DVD group compared with the control group [adjusted mean difference 0.28, 95% confidence interval (CI) 0.11 to 0.44; p < 0.001] and in the face-to-face physiotherapy group compared with the control group (adjusted mean difference 0.24, 95% CI 0.04 to 0.44; p < 0.05), with equivalence between the DVD and the face-to-face physiotherapy groups (adjusted mean difference 0.04, 95% CI -0.16 to 0.24). In all sensitivity analyses, both interventions remained significantly superior to the control and equivalence between the interventions was maintained. In other questionnaire outcome measures and in the physiological measures assessed, there were no significant between-group differences. Process evaluations showed that participants engaged well with both of the active interventions, but that some participants in the DVD arm would have liked to receive tuition from a professional. Asthma health-care costs were lower in both intervention arms than in the control group, indicating 'dominance' for both of the interventions compared with the control, with lowest costs in the DVD arm. The rate of adverse events was lower in the DVD and face-to-face physiotherapy groups than in the control group. Only 10% of the potentially eligible population responded to the study invitation. However, breathing retraining exercises improved QoL and reduced health-care costs in adults with asthma whose condition remains uncontrolled despite standard pharmacological therapy, were engaged with well by patients and can be delivered effectively as a self-guided intervention. The intervention should now be transferred to an internet-based platform and implementation studies performed. Interventions for younger patients should be developed and trialled. Current Controlled Trials ISRCTN88318003. This project was primarily funded by the NIHR Health Technology Assessment programme and will be published in full in Health Technology Assessment; Vol. 21, No. 53. See the NIHR Journals Library website for further project information. Additional financial support was received from Comprehensive Local Research Networks.